O perfil do Serviço de Atendimento Especializado - SAE, Goiânia – Goiás - Silveira, Jane Martins (2017)
The Specialized Assistance Service (SAE) is an important resource for health, since it offers the specialized treatment for the population of Goiânia city and the neighboring municipalities agreed with the Human Immunodeficiency Virus / Acquired Immunodeficiency Syndrome (HIV / AIDS ) patients. Through this study, it is possible to describe the target of this service by getting the percentage of users referred to the SAE; Data on the epidemiological profile of its users: sociodemographic profile, way of the transmission and clinical and laboratory profile, and the achievement of the millennium goals for 90% of people diagnosed with HIV in current treatment and 90% of those in treatmento with viral suppression, these goals of the United Nations-UN established a commitment to ensure the sustainability of our planet by signing with 192 countries the "Millennium Declaration" and one of its purposes was the fight against HIV/AIDS. The study targeted to answer the question "What is the profile of SAE-Goiânia, how long time is the demand of the city, who is its user, how is this people exposed and how to reach the mundial goals in the service?" It was a quantitative and descriptive. Data were collected from 182 SAE users in the secondary banks of the systems: Information System of Notification Appeal (SINAN-2015), Logistic Control System for Antiretroviral Medicines (SICLON-2016), Ambulatory Care System (SICAA-2016), files and documents from the SAE Pharmacy of the Reference Center for Diagnosis and Therapeutics (CRDT-2016). The results were: about the percentage of patients reffered to the SAE was 17.38% of the demand for diagnosed users living in Goiânia city, about the epidemiological profile the predominance of male gender was of 92.31%, the age group in both genders was between 20 to 34 years old in 65.4%. The most reported schooling was high school (30.2%) followed by not completed college education (17.0%). The most self-reported race in this study was brown (42.9%). About the behavioral aspects there was the predominance of heterosexual relations among women (78.6%) and homosexual relationships (50.0%) among men. Regarding the transmission of disease way, "sexual intercourse" predominated (88.3%) followed by other ways such as: blood (injecting drugs 2.7%) and vertical transmission (0.5%). The dropout rate was 4.4% of users of antiretroviral therapy (TARV). Regarding the suppression of the viral charge 60.5% of the users had an undetectable viral charge in the next year of beginning of treatment disease. It is concluded that the SAE, during the analyzed period, it has not yet reached the global targets related to 90% of people diagnosed with HIV in treatment on TARV and 90% of people in treatment with viral suppression. The knowledge of reality contributes to the improvement of the HIV/AIDS epidemiological surveillance system in our area, to describe the profile of the service provided and to reach the indicators for the two world goals 90-90-90, in the SAE it is a subsidy for the local managers in the structuring and/or readaptation of these services and focus on the actions aimed at the treatment and continuous care of users.